Enhancing climate advisory services in Kenya: a collaborative review of the MAM and OND 2025 seasons - Makokha, Sidjesse; Dhulipala, Ram (International Livestock Research Institute, 2025)
The Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) supported national mapping of livestock routes in Kenya and Ethiopia. The presentation describes the process undertaken.